S-Allylmercaptocysteine Targets Nrf2 in Osteoarthritis Treatment Through NOX4/NF-κB Pathway - Yang G; Sun S; Wang J; Li W; Wang X; Yuan L; Li S (Dove Medical Press, 2020)
Guang Yang,1 Shui Sun,1 Jian Wang,1 Wei Li,1 Xianquan Wang,1 Lin Yuan,1 Siying Li2 1Department of Joint Surgery, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan 250021, Shandong, People’s Republic of China; 2Department of Physiology & Pathophysiology, School of Basic Medical Sciences, Cheeloo College of Medicine, Shandong University, Jinan 250012, Shandong, People’s Republic of ChinaCorrespondence: Siying LiDepartment of Physiology & Pathophysiology, School of Basic Medical Sciences, Cheeloo College of Medicine, Shandong University, No. 44, Wenhua West Road, Jinan 250012, Shandong, People’s Republic of ChinaTel +86-186 5319 8899Email lisiying@sdu.edu.cnGuang Yang Email mayayangguang@163.comPurpose: This study aimed to explore the potential role and mechanism of garlic-derived S-allylmercaptocysteine (SAMC), the major water-soluble fraction of garlic, in osteoarthritis (OA) both in vivo and in vitro.Methods: The effect of SAMC in a surgical-induced OA model was examined by X-ray, staining, ELISA, and immunoblotting. Then the key role of Nrf2 by SAMC treatment in IL-1β stimulated chondrocytes in vitro was determined by gene-knockdown technique.Results: SAMC could stabilize the extracellular matrix (ECM) by decreasing metalloproteinase (MMPs) expression to suppress type II collagen degradation in OA rats. The inflammatory cytokines, such as IL-1β, TNF-α, and IL-6, were elevated in OA, which could be down-regulated by SAMC treatment. This effect was parallel with NF-κB signaling inhibition by SAMC. As oxidative stress has been shown to participate in the inflammatory pathways in OA conditions, the key regulator Nrf2 in redox-homeostasis was evaluated in SAMC-treated OA rats. Nrf2 and its down-stream gene NQO-1 were activated in the SAMC-treated group, accompanied by NAD(P)H oxidases 4 (NOX4) expression down-regulated. As a result, the toxic lipid peroxidation byproduct 4-hydroxynonenal (4HNE) was reduced in articular cartilage. In IL-1β-stimulated primary rat chondrocytes, which could mimic OA in vitro, SAMC could ameliorate collagen destruction, inhibit inflammation, and maintain redox-homeostasis. Interestingly, after Nrf2 gene knockdown by adenovirus, the protective effect of SAMC in IL-1β-stimulated chondrocytes disappeared.Conclusion: Overall, our study demonstrated that SAMC targeted Nrf2 to protect OA both in vivo and in vitro, which would be a new pharmaceutical way for OA therapy.Keywords: S-allylmercaptocysteine, Nrf2, osteoarthritis, oxidative stress, inflammation